(untitled) (Itinerarios Educativos, 2025)
In this article, we aim to analyze the institutional and pedagogical support for the educational trajectories of students with disabilities pursuing teaching degrees at the National University of Patagonia San Juan Bosco. In particular, we draw on interviews with members of the University Accessibility Commission, teachers, and heads of the teaching programs at the Faculty of Humanities and Social Sciences. By understanding and investigating the support from the perspectives of the institutional and teaching actors involved, we were able to identify various tensions, advances, and challenges regarding academic accessibility, the implementation of regulatory frameworks, and the practices enacted within pedagogical and institutional relationships. Although there are experiences of articulation and networking, these are largely sustained by the individual commitment of teachers and institutional leaders, in a context marked by institutional fragmentation and scarce resources. In this framework, there is a need to consolidate a university accessibility policy as a constitutive part of the right to higher education.